(untitled) (Journal of Parents and Teachers, 2026)
The approach proposed in the article is aimed at schools that are thriving and demonstrating vitality in their progress. It could be said that, if a school is truly thriving, it goes through five successive and flexible stages: creation, leadership, delegation, coordination and quality circles. This is a continuous process that transforms a school into a living reality in which all its members play an active part. The article describes each phase and proposes a guide, in the form of a game, for implementing them.